Popular City and Marginal City: The Poetry of Carlos Pezoa Véliz in Valparaíso [Ciudad Popular y Ciudad Marginal: La Poesía de Carlos Pezoa Véliz en Valparaíso] - Nomez-Diaz, N (Universidad de Playa Ancha de Ciencias de la Educacion, 2022)
This article shows the relationship that Carlos Pezoa Véliz’s poetry develops with the popular and marginal Valparaiso world, especially with the population from the city center close to the port and the port itself. In this perspective, the historic and cultural context of the poet life in Valparaíso is analyzed and the main features in the poems “Vida de puerto” and “Alma chilena”, written in different moments (1903 and 1908). In both texts, a change is shown which goes from a naturalistic and picturesque imaginary in the first poem, to the presentation of a narrator who identifies with an individual and collective popular world, in the second. During this evolution, the poetic characters are transformed into dissident voices which produces a novelty and original writing into the modern Chilean poetry. © 2022 Authors. All rights reserved.